THE USE OF VIRTUAL WORLD TOOLS BY ADOLESCENT GIRLS IN UZBEKISTAN DURING THE SOCIALIZATION PROCESS - Khatamov Boburjon Qosimjon o‘g‘li (American Journals Publishing, 2024)
Changes in a child's personality during adolescence. The attitude of representatives of the older generation to the changes in teenagers in the period when the tools of the virtual world became popular. The formation of competences in the correct use of virtual world tools is an important task for our society today.
Keywords: Virtual world tools, competencies of correct use of virtual world tools, cyber culture, teenage girls, adolescence.